2012
DOI: 10.1175/jhm-d-11-097.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Climate Change Impact on Mean Annual Runoff across Continental Australia Using Budyko and Fu Equations and Hydrological Models

Abstract: This paper presents the climate change impact on mean annual runoff across continental Australia estimated using the Budyko and Fu equations informed by projections from 15 global climate models and compares the estimates with those from extensive hydrological modeling. The results show runoff decline in southeast and far southwest Australia, but elsewhere across the continent there is no clear agreement between the global climate models in the direction of future precipitation and runoff change. Averaged acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 41 publications
3
57
0
3
Order By: Relevance
“…The Budyko water balance approach for estimating the climatic sensitivity has been widely applied in previous studies [8,[19][20][21][22]. However, studies relating groundwater (e.g., baseflow) to Budyko Hypothesis were relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…The Budyko water balance approach for estimating the climatic sensitivity has been widely applied in previous studies [8,[19][20][21][22]. However, studies relating groundwater (e.g., baseflow) to Budyko Hypothesis were relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have been applied at single basins (Donohue et al, 2011;Jiang et al, 2015;Liang and Liu, 2014;Liu and McVicar, 2012;Roderick and Farquhar, 2011;Xu et al, 2014;Zhang X. et al, 2014) or multiple basins within a single region: USA (Chen et al, 2013;Wang and Hejazi, 2011;Carmona et al, 2014;Istanbulluoglu et al, 2012), Australia (Donohue et al, 2010(Donohue et al, , 2012Teng et al, 2012), China (Yang D. et al, 2007(Yang D. et al, , 2009Yang and Yang, 2011;Yang H. et al, 2014;Cong et al, 2015;Xiong and Guo, 2012;Yu et al, 2013) and Europe (Velde et al, 2014;Oudin et al, 2008). The global scale studies have also been conducted but mainly focusing on the development of the Budyko functional forms (Koster and Suarez, 1999;Zhang L. et al, 2001;Arora, 2002) and their parameters (Li et al, 2013;Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A few examples include Teng et al (2012), who compared the Budyko runoff projections and hydrological model outputs driven by 15 GCMs over Australia. This study concluded that the Budyko equa-tion agrees with model projections over large regions, but underestimates runoff in wet regions and overestimates it in dry regions.…”
Section: Introductionmentioning
confidence: 99%
“…In southeastern Australia it has been projected that there will be a reduction in mean annual runoff of 10 % on average when different climate models are used as input to hydrological models (Cai and Cowan, 2008;Chiew et al, 2009;Roderick and Farquhar, 2011;Teng et al, 2012a;Vaze and Teng, 2011). These studies assessed the possible impacts of climate change on total runoff based on rainfall-runoff relationships which only considered first-order effects of changes in precipitation and temperature with subsequent impacts on evaporative demand.…”
Section: Z K Tesemma Et Al: Including the Dynamic Relationship Intmentioning
confidence: 99%